Direct shear testing of frozen soil-structure interface under high normal stress and frozen-thawing conditions - Bo Wang; Zhi-qiang Liu; Yu Bao (Soils and Foundations, 2025)
By using an improved DRS-1 high pressure direct shear test system, a series direct shear tests have been carried out under high normal stress and frozen-thawing conditions. Basic shear mechanical characteristics of the interface between the frozen soil and structure are summarized. Effects of normal stress and thawing temperature on the peak shear stress and the initial shear modulus are discussed. The results show that patterns of shear stress-displacement curve will transform gradually from strain softening to strain hardening as the thawing temperature increases. The peak shear strength of frozen soil-structure interface increases significantly with the increase of the normal stress, but decreases with the thawing temperature increases. High normal stress results in larger effective stress in the soil and hinders movement of soil particles on the interface. Increasing of the thawing temperature reduces the adfreezing force on the frozen soil-structure interface.